Soliton-Like Solutions of Three Non-isospectral Equations - 石教云 宁同科 张大军 (Journal of Shanghai University, 2005)
n-soliton-like solutions of three non-isospectral equations, the non-isospectral mKdV equation, the non-isospectral sine-Gordon equation and the non-isospeetral nonlinear Schroedinger equation were obtained by using the Hirota method.